BEYOND MOTIVATION AND HEAVY WORK INVESTMENT: THE CRITICAL ROLE OF BEHAVIORAL-FOCUSED SELF-LEADERSHIP IN ACHIEVING ACADEMIC RESEARCH PERFORMANCE - Napitupulu, Herta (DeReMa (Development Research of Management): Jurnal Manajemen, 2024)
Many studies highlight the influence of motivation on lecturers' research performance. However, further research is needed to understand the mechanism behind this relationship better. This research aims to determine how behavioral-focused self-leadership and heavy work investment mediate extrinsic and intrinsic motivation to improve academic research performance. Based on social cognitive theory, extrinsic and intrinsic motivation enable individuals to develop strategies and expend effort to achieve expected performance. Data was collected through an online survey involving lecturers at universities in Indonesia (N = 216). The instrument used in the form of a questionnaire was developed from several measuring tools that have been widely used and have been validated. Data analysis was carried out using PLS-SEM. Research findings reveal that behavioral-focused self-leadership directly influences academic research performance and mediates the relationship between academic extrinsic motivation and academic intrinsic motivation on academic research performance. Academic extrinsic and intrinsic motivation have a positive effect on heavy work investment. However, in this study, there is insufficient evidence to suggest that there is a significant influence between heavy work investment and academic research performance. These findings indicate that more than heavy work investment is needed to influence academic research performance significantly. These results expand our understanding of the existing literature on work motivation and self-leadership. These findings have implications for higher education management. Emphasis on developing behavioral-focused self-leadership strategies for lecturers' human resources will increase the effectiveness of heavy work investments and prevent mental health problems that workaholic tendencies may cause. Abstrak dalam Bahasa Indonesia Banyak penelitian menyoroti pengaruh motivasi terhadap kinerja penelitian dosen. Namun, penelitian lebih lanjut diperlukan untuk memahami mekanisme di balik hubungan ini dengan lebih baik. Penelitian ini bertujuan untuk menentukan bagaimana kepemimpinan diri yang berfokus pada perilaku dan investasi kerja yang berat memediasi motivasi ekstrinsik dan intrinsik untuk meningkatkan kinerja penelitian akademik. Berdasarkan teori kognitif sosial, motivasi ekstrinsik dan intrinsik memungkinkan individu mengembangkan strategi dan mengeluarkan usaha untuk mencapai kinerja yang diharapkan. Data dikumpulkan melalui survei online yang melibatkan dosen di universitas di Indonesia (N = 216). Instrumen yang digunakan berupa kuesioner dikembangkan dari beberapa alat ukur yang telah banyak digunakan dan telah divalidasi. Analisis data dilakukan menggunakan PLS-SEM. Temuan penelitian mengungkapkan bahwa kepemimpinan diri yang berfokus pada perilaku secara langsung memengaruhi kinerja penelitian akademik dan memediasi hubungan antara motivasi ekstrinsik akademik dan motivasi intrinsik akademik terhadap kinerja penelitian akademik. Motivasi ekstrinsik dan intrinsik akademik memiliki pengaruh positif terhadap investasi kerja yang berat. Namun, dalam penelitian ini, tidak ada cukup bukti yang menunjukkan adanya pengaruh signifikan antara investasi kerja yang berat dan kinerja penelitian akademik. Temuan ini menunjukkan bahwa investasi kerja yang berat saja tidak cukup untuk mempengaruhi kinerja penelitian akademik secara signifikan. Hasil ini memperluas pemahaman kita tentang literatur yang ada mengenai motivasi kerja dan kepemimpinan diri. Temuan ini memiliki implikasi bagi manajemen pendidikan tinggi. Penekanan pada pengembangan strategi kepemimpinan diri yang berfokus pada perilaku untuk sumber daya manusia dosen akan meningkatkan efektivitas investasi kerja yang berat dan mencegah masalah kesehatan mental yang mungkin disebabkan oleh kecenderungan kerja berlebihan.